Tabanidae (Diptera) holotypes in the KwaZulu-Natal Museum collection: Part 2. Diachlorini and Tabanini - Kirstin A. Williams; Louwrens P. Snyman (African Invertebrates)
All primary (name-bearing) and secondary types (paratypes) of Bartolomeudiasiella, Cydistomyia and Limata within the tribe Diachlorini and Hybomitra, Tabanus and Therioplectes within the tribe Tabanini, deposited in the KwaZulu-Natal Museum (NMSA) are documented: Cydistomyia (Amanella) cooksoni Usher, 1965; Cydistomyia (Amanella) grayi (Oldroyd, 1957), comb. nov.; Cydistomyia (Amanella) ignota Usher, 1965; Cydistomyia (Amanella) ingridina Usher, 1965; Cydistomyia (Amanella) shaka Usher, 1970; Cydistomyia (Amanella) zimbiti Usher, 1970; Limata kuhnelti Usher, 1967 [now Bartolomeudiasiella kuhnelti (Usher, 1967)]; Limata miranda Usher, 1968; Limata parafacialis Oldroyd, 1957; Tabanus crocodilinus Austen, 1912; Tabanus flavicoxa Usher, 1954; Tabanus nefas Usher, 1971; Tabanus postacutus Oldroyd, 1947; Tabanus saxicolus Usher, 1965 [now Hybomitra saxicolus (Usher, 1965)]; Therioplectes zumpti (Dias, 1956). The reference to the original publication, including the original name, the type locality and the collector, is provided for each species. In addition, brief remarks and colour photographs are provided. This is the second in a series of publications on the primary types of the Tabanidae of the KwaZulu-Natal Museum.